Low-temperature wetting mechanisms of polycrystalline chemical vapour deposition (CVD) diamond by Sn-Ti solder alloys. (15th November 2019) - Liao, Xinjiang; Mu, Dekui; Fu, Wei; Huang, Hui; Huang, Han
Abstract: Synthetic diamond is an important carbonous material that has widespread applications ranging from machine tools to the next-generation wafer of powder devices. Understanding of its wetting behaviours is therefore essential for the development of the highly required diamond bonding technique. In this paper, the wettability and spreading kinetics of Sn-Ti solder alloys were systematically investigated on polycrystalline chemical vapour deposition (CVD) diamond using the sessile drop method. In situ examination of contact angles at continuously elevated temperatures indicated that wetting of the CVD diamond by Sn-Ti solder alloys commenced at temperatures well below the bonding temperatures of conventional filler alloys. An excellent wetting of Sn-Ti solder alloy on the CVD diamond was induced by the addition of a small amount of Ti (0.5 wt%). It was also revealed that the spreading process of Sn-Ti alloys on the CVD diamond was initially controlled by the Ti adsorption at the wetting triple line. Enhancing the Ti adsorption at the wetting triple line could effectively improve the low-temperature wettability of Sn-Ti alloys on the CVD diamond, such as the case of 600 °C in this work, at which the possibility of surface corrosion and thermal damage of diamond devices can be substantially reduced. Graphical abstract: Unlabelled Image Highlights: Trace Ti addition induces a good wetting of Sn-Ti solder alloys on polycrystalline chemical vapour deposition (CVD) diamond. An adsorption wetting of polycrystalline CVD diamond by Sn-Ti solder alloys has been verified at 740-810 °C. Wettability of synthetic diamond was improved by enhancing the Ti adsorption at wetting triple line of Sn-Ti alloy at 600 °C.